Producción de las variedades de café ecorobusta, conilón y napopayamino (año 2) empleando microorganismos eficientes y abonos orgánicos. - Anchundia Suárez, Gissela Marianela (2023)
Coffee production is a great engine for the Ecuadorian economy since it provides revenue for the government which generates income for coffee growers, worldwide it is in third place after Brazil and Colombia, coffee is a crop that is part of the Ecuadorian identity since it is part of one of the oldest crops in the region, however, it is a crop that lacks technological alternatives as well as technical information on the different existing coffee varieties. The main objective of the research was to evaluate the production of Ecorobusta, Conilon and Napopayamino coffee varieties (year 2) using efficient microorganisms and organic fertilizers. A completely randomized block design (DBCA) was used with four treatments, two repetitions and five experimental units using a Tukey test at 5% probability. The treatments that were used were four distributed as follows T1=Control, T2 Bioabor, T3 Chemical mixture, T4 Chemical mixture + Biabor and in turn efficient microorganisms were used as a complement to fertilization. Before carrying out the investigation, a soil analysis was carried out and 440 g/plant of CaCO3 was applied. The variables evaluated were the following: plant height (m), stem diameter (cm), number of branches and production (g). As part of the results, the best results in terms of production values, the best production or harvest obtained was with the Conilón 4402.5 gr variety with the treatment of the chemical mixture. Concluding that the application of efficient microorganisms and organic fertilizers, with regard to the plant height variables, the best height was obtained in the Conilon variety with 3.10 (m), diameter of the stem register 102.44 (mm) and a total number of branches of 66.13 but in the Ecorobusta variety. Regarding the chemical composition of the soil after the incorporation of efficient microorganisms and organic fertilizers, slight changes were evidenced, such as in organic matter from 3.0% to 5.70%.